The Pragmatic Analysis of Cooperative Principle in Turning Red Movie - Chud Radeffy Azhari; Ambalegin Ambalegin (Institut Agama Islam Negeri Palopo, 2022)
This study examined several cooperative ideas expressed by characters in turning red movies using Grice's theory. This study used descriptive qualitative analysis to interpret the data. Observational methods and taking a note were used to collect the data by Sudaryanto. Following that, the data were analyzed using the Matching technique and the Pragmatic Identity Method to examine the data in context. The cooperation principle contained four types of maxims. There were 54 maxims of total in the data. It was discovered the results of maxim quantity with 13 data, 9 data maxim of quality, 3 data for the maxim of relevance, and maxim of manner with 9 data. Simple terms, the quantity maxim was the most widely used data piece. The maxim of relation was the smallest principle that the Turning red movie characters used.